Living in the new millennium : houses at the start of the 21st century - Cox, Maire (New York, N.Y. : Phaidon, 2009)
This book provides a concise overview of the best contemporary houses from around the world. It covers a wide range of housing types built by established architects, such as Shigeru Ban, John Pawson and Kengo Kuma, alongside emerging architectural talents
Includes index
Keywords: Architecture, Domestic -- 21st century; Architecture, Domestic -- Designs and plans